2019
DOI: 10.1002/jmri.26658
|View full text |Cite
|
Sign up to set email alerts
|

Water–fat separation and parameter mapping in cardiac MRI via deep learning with a convolutional neural network

Abstract: Background Water–fat separation is a postprocessing technique most commonly applied to multiple‐gradient‐echo magnetic resonance (MR) images to identify fat, provide images with fat suppression, and to measure fat tissue concentration. Recently, Numerous advancements have been reported. In contrast to early methods, the process of water–fat separation has become complicated due to multiparametric analytic models, optimization methods, and the absence of a unified framework for diverse source data. Purpose To d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 24 publications
1
43
0
Order By: Relevance
“…In this work, we adapted the approaches in recent works 13,14 and made W, F,f, and R2 the target output of the network. A U‐net type network ΨSi;θ with network weights θ is trained on M training pairs }{Si,ΨREF)(Si, where Si and normalΨREFSi=W,F,f,R2 are the input complex GRE signal and the corresponding reference T2‐IDEAL reconstruction (reference), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this work, we adapted the approaches in recent works 13,14 and made W, F,f, and R2 the target output of the network. A U‐net type network ΨSi;θ with network weights θ is trained on M training pairs }{Si,ΨREF)(Si, where Si and normalΨREFSi=W,F,f,R2 are the input complex GRE signal and the corresponding reference T2‐IDEAL reconstruction (reference), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In this work, we adapted the approaches in recent works 13,14 and made W, F, f , and R * 2 the target output of the network. A U-net type network Ψ S i ; with network weights is trained on M training pairs…”
Section: Std Water/fat Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…DL-based techniques have been recently proposed for automating myocardial T 1 , T 2 , and extra-cellular volume quantification 89,90 and water/fat separation. 91 DL has also been recently used for on-the-fly quality control-driven segmentation of myocardial T 1 mapping. 92 Despite the prognostic value of scar burden, scar quantification in cardiac MR is limited to research studies without standardization, and DL-based scar quantification has shown promise in scar quantification.…”
Section: Automated Cardiac Mr Image Analysis With DLmentioning
confidence: 99%